Geographical indicators (should we extend ourselves further?) - Spence, Malcolm
Indicates that the debate at the TRIPS Council on whether or not the kind of protection provided to Geographical Indicators (GIs) used on wines and spirits should be extended to (GIs) used on other products, has found itself bogged down. Looks at the issues from a perspective close to the level of the producers who will use GIs in the course of international trade than those currently being expressed at the TRIPS Council.